THE PILOT PROJECT OF DISTANT LEARNING IN ELEMENTARY SCHOOLS LOCATED FAR FROM ZADAR - Zekanović-Korona, Ljiljana (Array, 2006)
The national program of development of the islands is one of the priorities of the Croatian government and the Zadar region, and teaching at distance is one of the forms of promoting education on the islands. As on the islands of Zadar there is a lack of teaching staff qualified to teach all the subjects in the higher grades of elementary school, the pupils on the islands do not gain all the kinds of knowledge as do their coevals on land. The idea of the distant learning pilot project is that the teaching staff from Zadar starts taking part in modernization of the school education on the Zadar islands through distance learning. The central server system intended for the pilot project will be established at the University of Zadar. The lectures, which will be delivered by teachers in Zadar, will be transmitted in real time over the server system at the University and the CARnet network and Internet. The students will be able to hear the teacher and see the presentation of his/her lecture, and ask him/her questions and hear the answers in real time. The aim of this pilot project is to establish the efficiency of such a form of education, as well as the interest of both students and teachers in distance learning. This work will analyze all the details connected with starting of such a project.